Study on Home Chairs Design Evaluation for Low-and Middle-income Groups Based on User Experience - Leng, Xianshu; Zhang, Hong; Feng, Ding (International Journal of Scientific Research and Management (IJSRM), 2020)
Pay attention to the home living environment of low-and middle-income groups, study the user-centered design evaluation method to guide the design of home chairs suitable for low-and middle-income groups. Introducing Analytic Hierarchy Process（AHP）into home chairs’ design evaluation, it establishes a different layer and different elements structure model based on sensory experience, behavioral experience, emotional experience and economic experience from the point of user experience. Scoring each element, it calculates and determines the weight value of every element, and forms an evaluation method of home chairs for low-and middle-income Groups. Using the method to evaluate the design schemes of 3 home chairs, it obtains the optimal scheme. Then, surveying the market sales data to verify the accuracy of the result. The evaluation method consists of four major elements: sensory experience(B1), 27%; behavior experience(B2), 41%; emotional experience(B3), 10%; economic experience(B4), 22%. The method can effectively solve the complex comparison of multiple elements in design evaluation and provide a comprehensive method combining qualitative and quantitative methods for product design, and provides reference for products design and evaluation of the same type